2012
DOI: 10.1136/gutjnl-2011-301345
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor/c-Met signalling is important for the selection of transplanted hepatocytes

Abstract: HGF/c-Met plays a crucial role in host and donor cells of the liver for the cursiv selection of transplanted hepatocytes. Modulating HGF-dependent signalling seems a promising therapeutic option to favour expansion of transplanted hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Hepatocyte transplantation is currently considered as a promising alternative, especially once the yield and outcome of this technique can be improved. In our previous studies we demonstrated the feasibility of HT and identified responsible factors for donor cell selection in this model [13], [19].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Hepatocyte transplantation is currently considered as a promising alternative, especially once the yield and outcome of this technique can be improved. In our previous studies we demonstrated the feasibility of HT and identified responsible factors for donor cell selection in this model [13], [19].…”
Section: Discussionmentioning
confidence: 89%
“…For the generation of donor mice, Casp8 Δhepa and Casp8 loxP/loxP mice were crossed with human-α1-antitrypsin (hAAT) transgenic mice (C57/Bl6) (Casp8 Δhepa /hAAT(+); Casp8 loxP/loxP /hAAT(+)). The expression of the marker protein hAAT is controlled by a α1-antitrypsin-specific promoter to ensure hepatocyte-specific gene expression [13], [16]. At least four mice per group were treated and analysed in parallel for all experiments – that were repeated at least twice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite clinical improvements in patients, significant problems have arisen because of inefficient engraftment, death or ectopic distribution of cells that did not engraft in the target tissue, emboli formation, immunological rejection, and transient effects of transplanted cells [34][35][36]. A number of preconditioning regimens including irradiation or chemicals have been tried but discontinued for various reasons such as senescence, radiation hazards, or an increased risk of cancer [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The work by Kaldenbach et al 4 in the current issue of Gut begins to address these issues by investigating the relevance of hepatocyte growth factor (HGF)/c-Met signalling in vivo for hepatocyte repopulation after transplantation. The authors employed an experimental system that made use of c-Met (loxP/loxP) and hepatocyte-specific conditional c-Met knockout (c-Met−/−) mice as donors and/or recipients for hepatocyte transplantation.…”
mentioning
confidence: 99%